Japan’s vision of East Asian regionalism − toward soft balancing strategy - Bobowski, Sebastian (Economics of the 21st Century, 2014)
East Asia is undoubtedly the region of unprecedented scale of dynamism of events, both in the economic and political terms. Growing economic power of China is nowadays a serious threat to the traditional regional diplomatic leadership of Japan, which has internal problems. Mutual distrust boosted by historical resentment contributed to the constitution of competing visions of East Asian regionalism, drawing, on the one hand, on the realm of values as the foundation of a common identity, and solidarity, on the other, on different concepts of membership of the Southeast, and South Asian countries, including the representatives of Oceania. Promoted through the path of soft diplomacy, Japanese vision of a broad community, involving, in addition to ASEAN, democratic countries of the South and Oceania, built on the foundation of universal values of the Western world, provided a natural counterbalance to the narrower, more conservative, strictly Asian concept of China. The involvement of the core of ASEAN, namely Singapore, Vietnam, Malaysia, Japan, South Korea, Australia, and New Zealand, together with Canada, Mexico, Chile and Peru in the Trans-Pacific Partnership, is confronted with Chinese counter-proposal in the form of Regional Comprehensive Economic Partnership, which indicates that the soft strategy game has gone up to a higher level. The coming years will resolve the dilemma which vision of economic regionalism is more attractive and vital
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 80-91
Keywords: Japan; East Asian regionalism; soft balancing strategy; Japonia; wschodnioazjatycki regionalizm; strategia miękkiego równoważenia